THE PECULIARITIES OF EDUCATIONAL COMMUNICATION UNDER THE DISTANCE LEARNING MODE - TSARYK, Olga; RYBINA , Nataliia (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The article analyzes the features of educational communication in higher education institutions in the context of distance learning. It has been noted that the ultimate goal of educational communication is both the transfer of information and the formation of a certain system of students’ knowledge, skills and competencies . The objective of the article is to analyze the features of the model of educational communication as a classic element of the information and pedagogical environment in terms of distance learning on the basis of pedagogical constructivism, presented in modern domestic and foreign studies. It has been analyzed the concept of distance learning as a purposeful interactive process of higher education, based on scientific sources and the use of modern information and telecommunications technologies. The advantages of distance learning are emphasized, in particular extraterritoriality, synchronous and asynchronous modes of interaction of participants of educational process. Under the distance learning mode there is a practical mastering of information tools and communication technologies. It has been emphasized that distance learning provides access to various educational resources, gives an opportunity to receive education in a convenient, adequate and appropriate form for the student, helps to develop student abilities, provides data exchange, communicative activities based on professional and educational interests, training, retraining or change professional activity. The educational environment as a combination of offline and online structures in monocultural and multicultural space is studied. It is emphasized that with the development of information technologies the students’ communicative efficiency of increases, access to international resources is simplified. The change of the model of educational communication is substantiated, as a result of which there is an attraction of more sources of information and communication channels in the space of information flows. It has been made the conclusions about the change of information transfer technology in a modern higher education institution. The communication capabilities of the educational process in terms of distance learning depend on the means of transmitting information that meet the goals and objectives of learning. Changes in the regulation of educational communication, the modality of the learning process is to assess the information educational flow by the subject of learning in solving personal educational problems.